A stable high internal phase emulsion fabricated with OSA-modified starch: an improvement in β-carotene stability and bioaccessibility. Issue 9 (12th August 2019) - Yan, Chi; McClements, David Julian; Zou, Liqiang; Liu, Wei
Abstract : A high internal phase emulsion (HIPE) was firstly fabricated with octenyl succinic anhydride modified starch through simple shear dispersion. Abstract : A high internal phase emulsion (HIPE) was firstly fabricated with octenyl succinic anhydride modified starch through simple shear dispersion. The impact of the emulsifier level, pH, and ionic strength on the rheology, microstructure, interfacial properties, water binding and thermal stability of the HIPE was determined. The results indicated that HIPEs could be formed at a suitably modified starch concentration (≥3 wt%), a wider range of pH (3 to 7) and all test salt levels (0 to 400 mM NaCl). Encapsulation of a sensitive hydrophobic nutraceutical (β-carotene) within the HIPEs could improve its chemical stability under UV exposure, and the degradation ratio was fairly similar at all test pH values. The β-carotene stability and bioaccessibility during in vitro digestion were improved by encapsulation into HIPEs, but their values depended on pH to some extent. These results are useful for designing and fabricating modified starch-stabilized HIPEs which can be utilized in functional food and pharmaceutical applications.